2014
DOI: 10.3390/molecules191015638
|View full text |Cite
|
Sign up to set email alerts
|

Eckol Enhances Heme Oxygenase-1 Expression through Activation of Nrf2/JNK Pathway in HepG2 Cells

Abstract: Eckol isolated from Ecklonia stolonifera was previously reported to exhibit cytoprotective activity with its intrinsic antioxidant activity in in vitro studies. In this study, we characterized the mechanism underlying the eckol-mediated the expression of heme oxygenase-1 (HO-1). Eckol suppressed the production of intracellular reactive oxygen species and increased glutathione level in HepG2 cells. Eckol treatment enhanced the expression of HO-1 at the both level of protein and mRNA in HepG2 cells. Enhanced exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 35 publications
(44 reference statements)
3
39
0
Order By: Relevance
“…A number of studies have suggested that diverse protein kinases are involved in the signals that trigger Nrf2-Keap1 dissociation and the phosphorylation of Nrf2, as well as the antioxidant-induced activation of the Nrf2/HO-1 signaling pathway. For example, the phenolic glucoside gastrodin stimulated HO-1 expression through the activation of the p38 MAPK/Nrf2 signaling pathway (39), the flavonoid sulfuretin upregulation of the activity of HO-1 through the JNK/ERK/Nrf2 signaling pathway (40), the eckol induction of Nrf2-dependent HO-1 expression through the JNK and PI3K/Akt signaling pathways (41), and the induction of expression of HO-1 by prenylated flavone cudraflavone B mediated through the PI3K/Akt pathway (42). These findings prove that the role of each pathway in the activation of Nrf2/HO-1 signaling, and their molecular targets, may be specific to the stimulus and cell type.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested that diverse protein kinases are involved in the signals that trigger Nrf2-Keap1 dissociation and the phosphorylation of Nrf2, as well as the antioxidant-induced activation of the Nrf2/HO-1 signaling pathway. For example, the phenolic glucoside gastrodin stimulated HO-1 expression through the activation of the p38 MAPK/Nrf2 signaling pathway (39), the flavonoid sulfuretin upregulation of the activity of HO-1 through the JNK/ERK/Nrf2 signaling pathway (40), the eckol induction of Nrf2-dependent HO-1 expression through the JNK and PI3K/Akt signaling pathways (41), and the induction of expression of HO-1 by prenylated flavone cudraflavone B mediated through the PI3K/Akt pathway (42). These findings prove that the role of each pathway in the activation of Nrf2/HO-1 signaling, and their molecular targets, may be specific to the stimulus and cell type.…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols protect against oxidative stress by eliminating free radicals (53). Oxidative stress is attenuated by eckol via the upregulation of transcription factors including nuclear respiratory factor (NRF) and Forkhead box O3a, which directly regulate the ROS-scavenging enzymes HO-1 and MnSOD via NRF2/JNK, ERK, PI3K/AKT, and AMPK signaling pathways (26,54,55). Consistent with these ndings, we showed that eckol alleviates H 2 O 2 -induced oxidative stress by stimulating the expression of HO-1 and MnSOD via PI3K/AKT, P38, and AMPK signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The phenolic glucoside, gastrodin, has also been shown to stimulate HO-1 expression through the activation of the p38 MAPK/Nrf2 signaling pathway (38). In addition, eckol, a phlorotannin isolated from brown algae, has been shown to induce Nrf2-dependent HO-1 expression through the JNK and PI3K/Akt signaling pathways (39). These findings suggest that the role of each pathway in the activation of Nrf2/HO-1 signaling, and their molecular targets, may be specific to the stimulus and cell type.…”
Section: Discussionmentioning
confidence: 99%